1986
DOI: 10.1128/mcb.6.12.4611
|View full text |Cite
|
Sign up to set email alerts
|

Fine-structure analysis of the processing and polyadenylation region of the herpes simplex virus type 1 thymidine kinase gene by using linker scanning, internal deletion, and insertion mutations.

Abstract: Most eucaryotic mRNAs are polyadenylated. In higher eucaryotes, the sequence AATAAA is located 7 to 30 base pairs (bp) upstream from the site of processing and polyadenylation and is a critical part of the signal for processing and polyadenylation. Efficient cleavage and polyadenylation also require sequences downstream of polyadenylation sites. The herpes simplex virus type 1 thymidine kinase (tk) gene contains two copies of the AATAAA hexanucleotide and a GT box (18 of 19 consecutive residues are G or T) pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 38 publications
4
41
0
Order By: Relevance
“…It is likely that the apparent contradictions are attributable to differences in plasmid constructions and experimental designs. Significantly, no small linker scanning mutation within the more 5'-proximal element could prevent in vitro cleavage (57), a result similar to that found with downstream elements from other polyadenylation signals (30,58). This result suggests that the downstream regions within polyadenylation signals may contain functionally redundant elements (57).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It is likely that the apparent contradictions are attributable to differences in plasmid constructions and experimental designs. Significantly, no small linker scanning mutation within the more 5'-proximal element could prevent in vitro cleavage (57), a result similar to that found with downstream elements from other polyadenylation signals (30,58). This result suggests that the downstream regions within polyadenylation signals may contain functionally redundant elements (57).…”
Section: Discussionsupporting
confidence: 66%
“…7). Previous work has shown that readthrough RNAs accumulate as products of primary transcripts when polyadenylation is inefficient (9,27,30,48,58). An absence of increased levels of these large RNAs in mutant transfections might, thus, indicate that mutant primary transcripts are less stable than wild-type primary transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…2B) was generally conserved across eukaryotes, even though in budding yeast greater variation in these cis elements appears to be tolerated (Graber et al 1999). One notable feature of PAS is that, depending on exactly how the AAUAAA and DSE signals are positioned and defined, the actual site of poly(A) addition can vary by several to tens of nucleotides (Zhang et al 1986;Sheets et al 1990;Tian et al 2005). This is especially evident in yeast PAS, which, perhaps due to lower sequence conservation, do not accurately define the position of polyadenylation (Zhao et al 1999).…”
Section: Polyadenylation Signals and 39 Noncoding Rna (Ncrna) Sequencesmentioning
confidence: 99%
“…The common 3' terminus of the US10/ll/12 transcripts lies approximately 160 bp from the XbaI site in 1802 DNA. This reduction is unlikely to be a direct effect of the introduced sequences on mRNA processing since the signals required for efficient 3' end formation are contained within 40 to 50 bp beyond the poly(A) site of HSV mRNAs Zhang et al, 1986). One possibility is that transcriptional readthrough from the inserted sequences in vFJ7 and vFJl0 could lower the amount of USll mRNA available for translation either by production of anti-sense mRNA or transcriptional interference.…”
Section: Discussionmentioning
confidence: 99%